2023
DOI: 10.1167/iovs.64.10.18
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor TGF-β2 and Its Association With Intraocular Pressure in a Naturally Occurring Large Animal Model of Glaucoma

Abstract: Purpose Transforming growth factor (TGF)-β2 has been widely implicated in human glaucoma pathology. The purpose of this study was to determine the source of TGF-β2 in aqueous humor (AH) and its relationship with intraocular pressure (IOP) in an inherited large animal model of glaucoma. Methods Sixty-six glaucomatous cats homozygous for LTBP2 mutation, and 42 normal cats were studied. IOP was measured weekly by rebound tonometry. AH was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…However, studies have demonstrated that cells from the trabecular meshwork, through which aqueous humor is drained out at the iridocorneal angle, express an active TGF receptor complex and respond to exogenous TGFB2 (Medina-Ortiz et al 2013;Montecchi-Palmer et al 2017). This has been reported to result in increased synthesis of extracellular matrix proteins (ECM), accumulation of which increases resistance to aqueous outflow, leading to elevated intraocular pressure and glaucoma in both human and mouse (Zeimer et al 1998;Munemasa and Kitaoka 2012;Prendes et al 2013;Oikawa et al 2023). This knowledge, combined with (i) the histopathologic examination of trabecular meshwork (TM) biopsies from two microcoric brothers with elevated IOP, that revealed ECM accumulation (Tawara et al 2005), and (ii) an elevated concentration of TGFB2 in the aqueous humor of an individual with MCOR, implies that glaucoma associated with MCOR may be initiated by SOX21.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, studies have demonstrated that cells from the trabecular meshwork, through which aqueous humor is drained out at the iridocorneal angle, express an active TGF receptor complex and respond to exogenous TGFB2 (Medina-Ortiz et al 2013;Montecchi-Palmer et al 2017). This has been reported to result in increased synthesis of extracellular matrix proteins (ECM), accumulation of which increases resistance to aqueous outflow, leading to elevated intraocular pressure and glaucoma in both human and mouse (Zeimer et al 1998;Munemasa and Kitaoka 2012;Prendes et al 2013;Oikawa et al 2023). This knowledge, combined with (i) the histopathologic examination of trabecular meshwork (TM) biopsies from two microcoric brothers with elevated IOP, that revealed ECM accumulation (Tawara et al 2005), and (ii) an elevated concentration of TGFB2 in the aqueous humor of an individual with MCOR, implies that glaucoma associated with MCOR may be initiated by SOX21.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 This has been reported to result in increased synthesis of extracellular matrix proteins (ECM), accumulation of which increases resistance to aqueous outflow, leading to elevated IOP and GLC in human, primates, cats and mouse. 912,41…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations